P-011 Preliminary results with a new volumetric-filling platinum coil, the penumbra coil 400. (12th July 2011) - Woo, H; Fiorella, D; Han, P
Abstract : Purpose: The FDA has recently approved the Penumbra Coil 400 for embolization of cerebral aneurysms. It is differentiated from existing platinum coils by virtue of its 0.020″ outer diameter, which results in increased filling per coil and intrinsic softness. We report the preliminary results of peri-procedural efficacy and safety of this new coil platform at two centers. Methods and Materials: This study is a retrospective case review of 7* consecutive patients at two centers treated with the Penumbra Coil. Adjunctive devices were used in 5 cases. The number of coils used to treat the aneurysm, the degree of occlusion and the final estimated packing density were recorded. Peri-procedural device related and clinical adverse events were recorded. Results: There were no device-related or clinical adverse events. An average of 4.4 coils (range 2–7) were deployed per aneurysm. The average final estimated packing density was 35.7% (range 15.1–48). 5 out of 7 aneurysms were completely occluded at the end of the procedure. Conclusions: The Penumbra Coil 400 can be successfully used to treat a wide range of aneurysm types and sizes with acceptable complete occlusion rates, final packing densities, and peri-procedural complications. It appears that fewer coils can be used to achieve these results than would be normally expected with conventional size coils. The effect on procedure time, flouro time, economics, and long term stability will require further study.